2017
DOI: 10.1002/ijop.12468
|View full text |Cite
|
Sign up to set email alerts
|

Factorial and convergent validity of the Youth Psychopathic Traits Inventory‐Short Version in Ghana

Abstract: Studies have shown the existence of psychopathy construct in Western cultures. However, there is a general lack of research on this topical issue in non-Western countries, specifically sub-Saharan Africa. Consequently, this study investigated the factorial and convergent validity of the Youth Psychopathic Traits Inventory-Short Version (YPI-S) in 327 adolescents in Ghana. Confirmatory factor analysis supported a three-factor structure (interpersonal, behavioural and affective) of psychopathy that was invariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…In addition, juveniles with high scores on all three dimensions of the YPI-S (psychopathic-like juveniles) showed more conduct problems and offenses than their non-psychopathic-like counterparts. In line with the original 50-item YPI, these results were found in both the general population and offender samples of both genders [ 1 , 16 , 18 , 27 , 30 , 47 50 , 58 , 62 ].…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, juveniles with high scores on all three dimensions of the YPI-S (psychopathic-like juveniles) showed more conduct problems and offenses than their non-psychopathic-like counterparts. In line with the original 50-item YPI, these results were found in both the general population and offender samples of both genders [ 1 , 16 , 18 , 27 , 30 , 47 50 , 58 , 62 ].…”
Section: Introductionsupporting
confidence: 84%
“…Items are rated on a 4-point Likert scale ranging from 1 = does not apply at all to 4 = applies very well. As mentioned in the introduction, the reliability and validity of the YPS-S are promising and seem to be in line with the original 50-item YPI [ 1 , 14 , 16 , 18 , 27 , 30 , 47 50 , 58 , 62 ].…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…Each item is rated on a 4‐point Likert scale (0 = does not apply at all , to 4 = applies very well ). The factor structure of the YPI‐S has been investigated in Ghana and a three‐factor structure (interpersonal, behavioural and affective) was confirmed (Adjorlolo and Watt, in press). The interpersonal factor includes grandiosity and ‘manipulativeness’, the behavioural domain consists of irresponsible and sensation seeking behaviours and the affective factor measures ‘callous‐unemotional’ traits and lack of remorse.…”
Section: Methodsmentioning
confidence: 99%
“…This has been referred to as an etic criterion: use of a specific "outsider" set of criteria as universally valid and reliable (Kaiser, Kohrt, Keys, Khoury, & Brewster, 2013). In Kenya and other lowand middle-income countries (LMICs), studies have largely focused on this etic approach, validating screening tools developed in the US to detect common mental disorders (Adjorlolo & Watt, 2017;Ali, Ryan, & De Silva, 2016). However, studies in African contexts have shown mixed results in terms of validity, highlighting limitations of relying solely on etic criteria (Ali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%